A MULTIDISCIPLINARY APPROACH TO CHARACTERIZE TRITICALE ELITE LINES FOR INDUSTRIAL USES - Cantale, Cristina; Belmonte, Alessandro; Correnti, Angelo; Farneti, Anna; Felici, Fabio; Gazza, Laura; Latini, Arianna; Nocente, Francesca; Micheli, Carla; Petrazzuolo, Francesco; et al. (Plant Breeding and Seed Science, 2018)
Plant biomass and organic wastes from agriculture represent an effective resource to be exploited for a sustainable rural development, optimizing the land use, diversifying rural entrepreneurship, producing energy and new income. Among crops, triticale is considered particularly interesting, showing several advantages such as high grain yield even in marginal environments, tolerance to drought, tolerance to more acid soils, lower production costs and lower susceptibility to biotic stresses. In the frame of a long collaboration with CIMMYT (International Maize and Wheat Improvement Center- MX), eight triticale elite lines from Mexico were grown in Italy using marginal lands. An Italian triticale variety and a bread wheat line, specifically bred for bioenergy applications, were used for comparison. Over three growing seasons, different agronomic evaluations were obtained harvesting at milk phase. In the third growing season, a set of parcels was harvested also at maturity, to evaluate grain yields and quality parameters from seeds. Milk phase biomass were properly dried and characterized following reference procedures, then used as substrate for anaerobic digestion to produce biogas and methane in lab-scale experiments. Seeds from interesting lines were used to test different quality parameters including falling number in order to evaluate the fermentation ability. RAPD technique by two different panels of primers was used to genotype a selection of lines.